Neuronal Differentiation of Human Glioma Cells Induced by Parthenolide Under In Vitro Conditions - Zhaoqi Tang; Chang Cao; Weiwei Tang; Yanrong Ye; Zhenhui Chen; Yun Shen (Biomedicines)
Objective: Previous drug repositioning studies have suggested that parthenolide may be a differentiation-inducing agent for glioma cells. This study aimed to experimentally verify the neuronal differentiation-inducing effects and proliferative impact of parthenolide on human glioma cells and explore its potential mechanisms. Methods: HE staining was used to observe the morphological changes in human glioma cell lines U87 and A172 induced by parthenolide. Immunocytochemistry was conducted to detect the expression of differentiation markers. The Ki-67 detection and CCK-8 assay were used to assess the effects of parthenolide on cell proliferation. The sphere formation assay was conducted to evaluate the self-renewal. Glioma stem cells (GSCs) derived from U87 cells were utilized to assess the ability of parthenolide to induce differentiation in GSCs. Western blot was used to detect the expression of histone deacetylase 1 (HDAC1). Bioinformatics analysis based on the CGGA database was conducted to evaluate the role of HDAC1 in glioma. Results: Parthenolide (4 μM) altered the morphology of U87 and A172 cells, as elongated cell projections were observed. Parthenolide induced glioma cells to express neuronal markers NeuN, MAP2, SYP, and NEFL, but not astrocyte or oligodendrocyte markers. Parthenolide significantly inhibited proliferation and self-renewal in glioma cells. Similar effects were observed in U87 GSCs. Furthermore, parthenolide downregulated HDAC1 expression in glioma cells, and the bioinformatics analysis revealed a potential relationship between neuronal characteristics and low expression of HDAC1 in glioma. Conclusion: Parthenolide induced neuronal differentiation and inhibited the cell proliferation in human glioma cells, which might be associated with the inhibition of HDAC1.